1996
DOI: 10.1111/j.1365-2230.1996.tb00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial juvenile systemic granulomatosis (Blau's syndrome)

Abstract: Blau's syndrome refers to the rare familial presentation of a sarcoid-like granulomatous disease classically involving the skin, uveal tract and joints, in the absence of pulmonary manifestations. The onset is in childhood, and the mode of inheritance is thought to be autosomal dominant. We report a 15-year-old female and her 22-month-old daughter who presented with clinical features similar to those of Blau's syndrome. In addition to the skin, eye and joint disease, the mother also developed neurological invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…128 In one study, DNA sequences coding for the mycobacterial 65 kDa antigen were found in 11 of 35 cases of sarcoidosis, 129 while in a more recent study, using only cutaneous specimens, mycobacterial DNA was demonstrated by PCR in 16 of 20 cases. 136 Camptodactyly is another defining sign. 130 Other findings supportive of a mycobacterial etiology are the beneficial effects of long-term tetracyclines 131 and the activation of a case following concurrent M. marinum infection of the skin.…”
Section: Introductionmentioning
confidence: 99%
“…128 In one study, DNA sequences coding for the mycobacterial 65 kDa antigen were found in 11 of 35 cases of sarcoidosis, 129 while in a more recent study, using only cutaneous specimens, mycobacterial DNA was demonstrated by PCR in 16 of 20 cases. 136 Camptodactyly is another defining sign. 130 Other findings supportive of a mycobacterial etiology are the beneficial effects of long-term tetracyclines 131 and the activation of a case following concurrent M. marinum infection of the skin.…”
Section: Introductionmentioning
confidence: 99%
“…2,4,27,30,34,55 Histologically, the naked noncaseating granulomas of EOS/BS involve primarily the upper dermis and often have a perifollicular distribution. 24,54 This histologic pattern is identical to that of lichen scrofulosorum, a tuberculid that is usually seen in children with tuberculosis that involves the lymph nodes and bones. Lichen scrofulosorum also has a clinical appearance similar to that of EOS/BS, although it favors the trunk rather than the extremities and face.…”
Section: Commentmentioning
confidence: 57%
“…52 They tend to be arranged in clusters or linear arrays but can become confluent, and a perifollicular distribution may be evident. 3,4,14,24,27,32,53,54 Intermittent episodes of widespread skin disease with spontaneous resolution usually occur during a period of years (in contrast to the more persistent skin lesions of sarcoidosis). Poikiloderma has been observed in older patients, 13,27 and pitted scars due to follicular atrophoderma are sometimes apparent at sites of previous inflammatory papules.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the following years, several familial cases were reported [31][32][33][34][35][36][37], and Tromp et al mapped the disease locus on the chromosomal region 16q12.1-13 by means of a linkage analysis of a large pedigree in 1996 [38]. Afterwards, additional descriptions of BS were reported [39][40][41][42][43][44][45], and five years later, Miceli-Richard et al identified three missense mutations represented by R334Q, R334W, and L469F NOD2 substitutions in the NACHT region [46]. From that time until today, several patients with BS and EOS have been described , and different NOD2 mutations have been found not only in BS (Table 1) but also in EOS ( Table 2).…”
Section: Historical Hints: From Familial Cases To the Identification mentioning
confidence: 97%